Experimental validation of lift and drag forces on an asymmetrical hydrofoil for seafloor anchoring applications. (January 2019) - Byrne, Gerry; Persoons, Tim; Kingston, William
Tidal power can be described as harnessing the kinetic energy of the in and out flows known as tides created by the changing gravitational pull of the moon and the sun on the oceans of the world. As the relative positions of the sun and moon can be accurately predicted, so can the resultant tidal movements, making tidal energy such a valuable resource and an attractive option for renewable power generation. However, the high costs and difficulties associated with the deployment of underwater turbines, which includes anchoring, are prohibitive factors in the widespread utilisation of tidal power technology. Existing turbine fixation methods are primarily based on the use of large gravity anchors or monopole structures to secure the turbine to the seabed. In an effort to reduce size, environmental impact on the seafloor and installation cost, a hydrofoil-based anchor could be considered. The objective of this study is to experimentally test the lift and drag force behaviour of a finite-span hydrofoil with endplates, whose profile was selected based on simplified two-dimensional (2D) numerical simulations using the vortex panel method. A customised lift and drag force measurement system for this prototype hydrofoil was designed, fabricated and calibrated, and subsequently installed and tested in the Dutch Tidal Testing Centre (TTC) in Den Oever, the Netherlands. A series of tests with force and flow velocity measurements are described for different angles-of-attack under realistic tidal flow conditions. Results for the lift and drag coefficients as a function of angle-of-attack are compared to numerical simulation data and revealed that the real-world lift force is predicted well, whereas the drag force is underpredicted by the numerical predictions. These findings provide useful information for the design of anchoring systems based of hydrofoil profiles.